2019
DOI: 10.1111/liv.14300
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA 91H overexpression contributes to the growth and metastasis of HCC by epigenetically positively regulating IGF2 expression

Abstract: are contributed equally to this work.Abbreviations: ChIP, Chromatin immunoprecipitation; H3K27me3, H3 lysine 27 trimethylation; H3K4me3, H3 lysine 4 trimethylation; HCC, Hepatocellular carcinoma; IGF2, Insulin-like growth factor 2; lncRNAs, Long noncoding RNAs; MANT, the matched adjacent nontumourous tissues; MTT, the methyl thiazolyl tetrazolium; NALT, the normal adult liver tissues;Neg-ctrl, negative control cells; PI, propidium iodide; PRC2, polycomb repressive complex 2; RIP, the RNA immunoprecipitation; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It is predominantly expressed from the maternal allele in human and mouse within the H19 gene region. In HCC tissue and cells, 91H is overexpressed [42]. High 91H expression is associated with a poor prognosis in HCC patients: both disease-free survival time and the overall survival time was shorter compared to patients with low 91H expressions [42].…”
Section: Lncrna 91hmentioning
confidence: 95%
See 1 more Smart Citation
“…It is predominantly expressed from the maternal allele in human and mouse within the H19 gene region. In HCC tissue and cells, 91H is overexpressed [42]. High 91H expression is associated with a poor prognosis in HCC patients: both disease-free survival time and the overall survival time was shorter compared to patients with low 91H expressions [42].…”
Section: Lncrna 91hmentioning
confidence: 95%
“…In HCC tissue and cells, 91H is overexpressed [42]. High 91H expression is associated with a poor prognosis in HCC patients: both disease-free survival time and the overall survival time was shorter compared to patients with low 91H expressions [42]. In vitro studies revealed that a knockdown of 91H in Hep3B cells down-regulated the expression of insulin-like growth factor 2 (IGF2) suggesting a co-regulation of 91H and IGF2 [42].…”
Section: Lncrna 91hmentioning
confidence: 99%
“…Consequently, LINRIS knockdown weakens downstream effects of IGF2BP2, particularly MYC-mediated glycolysis in CRC cells and proliferation of cancer cells. On the other hand, lncRNA 91H, a long non-coding antisense transcript located at H19/IGF2 locus, participates in tumor development [101,102]. lncRNA 91H silencing modulates proliferation, migration, invasion, autophagy and expression of mammalian target of rapamycin (mTOR) in CRC cancer cells by suppressing IGF2 expression, which up-regulates the expression of IGF2BP2 [103].…”
Section: Igf2bp2 and Lncrnas In Cancersmentioning
confidence: 99%
“…In recent years, a number of studies have reported that aberrant expression of lncRNAs is related to hepatocarcinogenesis [15][16][17]. LncRNAs, a heterogeneous group of RNA transcripts with a length of more than 200 nucleotides, are generally regarded as lacking proteincoding roles [3].…”
Section: Discussionmentioning
confidence: 99%